Integrated technique to produce sustainable bioethanol from lignocellulosic biomass - Monir, Minhaj Uddin; Azrina, Abd Aziz; Yousuf, Abu (Elsevier B.V., 2022)
This study focuses on the utilization of mostly available renewable energy resources, such as lignocellulosic biomass, to generate syngas and bioethanol through a hybrid gasification and syngas fermentation process. The lignocellulosic biomass was characterized using TGA, XRD, FESEM with EDX analysis, and gasifying parameters were optimized using Aspen Plus®. In the first stage of this integrated process, hydrogen-containing syngas was generated, and the final product was bioethanol. The forest waste-based syngas produces higher bioethanol than EFB and coconut shell in the presence of biocatalyst. Therefore, bioethanol will be a sustainable biofuel that will satisfy the world's future energy demands.